ADB Distinguished Speaker Lecture <subtitle>The Complementarity Between Cities and State Capacity</subtitle> - EDWARD L. GLAESER (Asian Development Review)
Public capacity complements urban density because externalities abound in cities and urban scale makes it possible to share infrastructure that needs to be managed. Yet, urban governments face limitations that are not experienced by private sector entities. A city cannot just stop policing if it decides it is bad at policing. Typically, public compensation and personnel policies are highly regulated either by law or by union contracts. City governments do, however, have one great advantage over private entities: a greater ability to learn from their peers. City governments do similar things throughout the world, while companies frequently specialize. Private companies have strong incentives to hide the trade secrets that make them more productive, cities do not. As individual cities do not have an incentive to make it easier for other governments to learn from them, multinational entities like the Asian Development Bank and the World Bank could enable that learning. Since climate-change-related crises are relatively rare events, city-to-city learning seems particularly important for adapting to climate change.